2019
DOI: 10.1149/2.0111903jss
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Micro-Sized Copper Columns Using Localized Electrochemical Deposition with a 20 μm Diameter Micro Anode

Abstract: This paper studies the effects of applied potential on the LECD process. which are critical for microelectromechanical systems and semiconductor-related applications. The structures and morphologies of the copper columns can be varied by changing the voltage between the anode and cathode, and high voltage leads to complex structures and morphology. Additionally, the cross section of copper columns was investigated to evaluate the quality of internal structure of columns, and the voids were appeared and the sha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 25 publications
0
4
2
Order By: Relevance
“…Wang et al. [ 43 ] suggested a direct relationship between the morphology and the applied voltage, yet in our study, we observe a wide range of morphologies for a single voltage difference, both in LECD and HLECD. We find from our experiments two primary culprits for these irregularities.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…Wang et al. [ 43 ] suggested a direct relationship between the morphology and the applied voltage, yet in our study, we observe a wide range of morphologies for a single voltage difference, both in LECD and HLECD. We find from our experiments two primary culprits for these irregularities.…”
Section: Discussioncontrasting
confidence: 66%
“…The surface morphology (the "blobby" nature of the surface, as clearly evident in Figure 4a) remains irregular and somewhat inconsistent throughout the printing process. Wang et al [43] suggested a direct relationship between the morphology and the applied voltage, yet in our study, we observe a wide range of morphologies for a single voltage difference, both in LECD and HLECD. We find from our experiments two primary culprits for these irregularities.…”
Section: Discussioncontrasting
confidence: 64%
“…[20,21] Wang et al studied the effect of applied potential on the structure and morphology changes of copper pillars during electrodeposition and proposed that high voltage leads to complex structures and morphology, which is crucial for MEMS and semiconductor-related applications. [22] Chen et al studied the influence of microtubule diameter, bias voltage, and electrolyte concentration on the deposition results by establishing a mathematical model and using the method of multiphysical field simulation. At the same time, they monitored the ion current in the electrodeposition process to judge the contact point and manufacturing quality.…”
Section: Introductionmentioning
confidence: 99%
“…However, most of the aforementioned studies have focused on column deposition [30] and the production of extended structures [31]. In 2000, Johansson et al used LECD to prepare a nickel column and deposited a portal made by bridging two separately built structures [32], but the joining structure was not fully formed.…”
Section: Introductionmentioning
confidence: 99%